Magnetic-sublevel population and alignment for the excitation of H- and He-like uranium in relativistic collisions - Gumberidze, Alexandre; Fritzsche, S.; Hagmann, S.; Kozhuharov, C.; Ma, X.; Steck, M.; Surzhykov, Andrey; Warczak, A.; Stöhlker, Thomas (Physical review. A, Atomic, molecular, and optical physics, 2011)
We have measured the alignment of the L-shell magnetic substates following the K-shell excitation of hydrogen- and helium-like uranium in relativistic collisions with a low-Z gaseous target. Within this experiment, the population distribution for the $L$-shell magnetic sublevels has been obtained via an angular differential study of the decay photons associated with the subsequent deexcitation process. The results show a very distinctive behavior for the H- and He-like heavy systems. In particular, for $K\ensuremath{→}L$ excitation of He-like uranium, a considerable alignment of the $L$-shell levels was observed. A comparison of our experimental findings with recent rigorous relativistic predictions provides a good qualitative and a reasonable quantitative agreement, emphasizing the importance of the magnetic-interaction and many-body effects in the strong-field domain of high-$Z$ ions.
Gesehen am 20.07.2022